Botulinum toxin-A injection into the anterior belly of the digastric muscle for the prevention of post-operative open bite in class II malocclusions: a case report and literature review - Yei-Jin Kang; Bong Kuen Cha; Dong Soon Choi; In San Jang; Seong-Gon Kim (SpringerOpen, 2019)
Abstract Background Class II malocclusion patients with hyperdivergent facial types are characterized by short mandibular body lengths and anterior open bite. Accordingly, the treatment for hyperdivergent skeletal class II malocclusion is a lengthening of the mandibular body length and a counterclockwise rotation of the mandible. To prevent post-operative relapse, botulinum toxin-A (BTX-A) injection can be a retention modality. Case presentation A class II open-bite patient received BTX-A injection to the anterior belly of her digastric muscle for the prevention of post-operative relapse. The relapse was evaluated via a clinical examination and a lateral cephalometric radiograph after the completion of post-surgical orthodontic treatment. The patient showed stable occlusion without any signs of relapse at 15 months post-operatively. Conclusion In this case presentation, a single injection into the anterior belly of the digastric muscle was sufficient for the prevention of post-operative open bite.